Stereoselective synthesis and antiproliferative activity of allo-gibberic acid-based 1,3-aminoalcohols regioisomers - Khdar Zein Alabdeen; Le Minh Tam; Schelz Zsuzsanna; Zupkó István; Szakonyi Zsolt (2024)
A new library of allo -gibberic acid-based aminoalcohol regioisomers was synthesised stereoselectively starting from commercially available gibberellic acid, which yields allo -gibberic acid under mild acidic conditions. The successful formation of hydroxymethyl...
Keywords: Farmakológia és gyógyszerészet